2019
DOI: 10.1002/biof.1592
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Circular RNA ANKRD36 attends to lipopolysaccharide‐aroused MRC‐5 cell injury via regulating microRNA‐31‐3p

Abstract: Background Some circular RNAs (circRNAs) are reported to attend to the pathogenesis of pneumonia. This study tested the impact of circRNA ankyrin repeat domain 36 (circANKRD36) on human embryonic lung fibroblast MRC‐5 cell injury irritated by lipopolysaccharide (LPS). Methods After LPS irritation, viability, apoptosis, ROS, protein, and cytokines, along with circANKRD36 were tested by CCK‐8, Annexin V‐FITC, DCFH‐DA, and ELISA or Western blot. si‐circANKRD36 and microRNA‐31‐3p/5p (miR‐31‐3p/5p) inhibitor were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…MiR-31-3p was found to target MyD88, therefore downregulating the NF-κB pathway. Thus, apoptosis and ROS production observed in LPS-treated MRC5 were caused, at least in part, by the circANKRD36 binding with miR-31-3p that impeded the miRNA downregulation of the NF-κB pathway [199].…”
Section: Mirnas and Oxidative Stress In Both Cardiac And Pulmonary DImentioning
confidence: 97%
“…MiR-31-3p was found to target MyD88, therefore downregulating the NF-κB pathway. Thus, apoptosis and ROS production observed in LPS-treated MRC5 were caused, at least in part, by the circANKRD36 binding with miR-31-3p that impeded the miRNA downregulation of the NF-κB pathway [199].…”
Section: Mirnas and Oxidative Stress In Both Cardiac And Pulmonary DImentioning
confidence: 97%
“…reported that circRNA vacuolar ATPase assembly factor (circVMA21) protected WI‐38 cell from lipopolysaccharide (LPS)‐triggered inflammatory injury possibly by regulating microRNA (miRNA)‐142‐3p and nuclear factor‐κB (NF‐κB) signaling . Guo and colleagues revealed that the knockdown of circRNA ankyrin repeat domain 36 (circANKRD36) relieved LPS‐evoked cytotoxicity in MRC‐5 cells via sponging miRNA‐31 and regulating myeloid differentiation factor 88 (MyD88) . As for circ_0038467, derived from the back‐splicing of ubiquinol‐cytochrome‐c reductase core protein 2 (UQCRC2), it was found to be significantly upregulated in neodymium oxide‐induced 16HBE cell line using the microarray circRNA analysis .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, circANKRD36 may be used as a biomarker for screening chronic inflammation in patients with T2DM (54) . Another study showed an association between pneumonia pathogenesis and circANKRD36 (55) . Irritated MRC-5 cell injury by lipopolysaccharide (LPS) evoked circANKRD36 to activate the NF-κB signaling pathway and caused inflammation in MRC-5 cells.…”
Section: Discussionmentioning
confidence: 99%